Diversity of metazoan parasites in Pellona flavipinnis (Valenciennes, 1836) (Clupeiformes: Pristigasteridae) from a Brazilian Amazon floodplain lake (Acta Scientiarum. Biological Sciences, 2025)
The structure of the parasitic infracommunity of Pellona flavipinnis, a carnivorous fish species of economic and ecological importance in the Amazon region, was characterized. Fifty-five P. flavipinnis specimens were collected in Catalão lake, euthanized, and necropsied for metazoan parasite examination. Of these, 41 P. flavipinnis specimens were parasitized. A total of 249 metazoans from five taxonomic groups were identified: Myxozoa (Myxobolus sp.) in the gills and operculum; Digenea, (Austrodiplostomum compactum) in the eyes; Acanthocephala (Neoechinorhynchus (Neoechinorhynchus) pellonis) in the intestine; Nematoda (Anisakis sp.) in the liver, stomach, and intestine and Branchiura (Argulus angelae) on the tegument. Pellona flavipinnis is reported here as a new host for all five parasite species. Anisakis sp. showed the highest prevalence value, followed by N. (N.) pellonis. The parasitic community was dominated by Anisakis sp., which exhibited the greatest importance index. Pellona flavipinnis parasitic fauna comprised one secondary species and four satellite species. No significant relationship was found between parasite abundance or richness and host body size.